Common variable immunodeficiency in a patient with Noonan syndrome - Özdemir, Öner; Dikici, Ümmügülsüm; Önata, Ece Tüsüz; Polat, Recep (Alergologia Polska - Polish Journal of Allergology, 2025)
Noonan syndrome is a disease that occurs in 1 in 1,000–2,500 live births, mostly inherited in an autosomal dominant manner. Noonan syndrome is a clinically and genetically heterogeneous disease that may be accompanied by growth retardation, prominent facial dysmorphic features, congenital heart defects, hypertrophic cardiomyopathy, skeletal anomalies, bleeding diathesis, ectodermal anomalies, lymphatic dysplasias, cryptorchidism, and cognitive disorders. Some of the patients with NS may experience various clinical issues related to immunodeficiency, such as recurrent infections. This article discusses a very rarely seen case of a 15-year-old male patient with Noonan syndrome having common variable immunodeficiency disease.